Perspective—Mesoscale Physics in the Catalyst Layer of Proton Exchange Membrane Fuel Cells. Issue 7 (1st January 2019) - Grunewald, Jonathan B.; Mistry, Aashutosh N.; Verma, Ankit; Goswami, Navneet; Mukherjee, Partha P.; Fuller, Thomas. F.
Abstract : Proton-exchange membranes fuel-cells (PEMFC) electrochemical performance insights are predicated on a detailed understanding of species transport in the cathode catalyst layer (CCL). Traditionally, CCL microstructure considerations were approached through approximations with unresolved pore-scale features. Such simplifications cause the loss of predictability for improving the economic feasibility via lower Pt-loading or non-noble metal catalysts. With advances in visualization, microstructure resolved mesoscale models become possible. A judicious combination of lattice Boltzmann (LBM) and finite volume (FVM) is an appropriate strategy for direct numerical simulation (DNS) of the physicochemical fields that remain unresolved due to spatiotemporal limitations.